Akzeptanzorientiertes Application Lifecycle Management - Hallerstede, Stefan; Danzinger, Frank; Bullinger-Hoffmann, Angelika; Möslein, Kathrin (HMD : Praxis der Wirtschaftsinformatik, 2011)
Zahlreiche Softwareprojekte in Unternehmen scheitern bereits kurz nach der Einführungsphase. Ein wesentlicher Grund hierfür ist mangelnde Akzeptanz durch die Nutzer. In diesem Artikel werden die Konsequenzen der Akzeptanzproblematik für das IT-Management mittels Application Lifecycle Management (ALM) beschrieben. Der Bedeutungsschwerpunkt bei akzeptanzkritischen Anwendungen – im Gegensatz zu unternehmenskritischen Anwendungen – verschiebt sich auf die Phasen Anforderungen, Design, Betrieb und Optimierung. Die Erprobung des Konzepts bei der agilen Entwicklung einer web-basierten Anwendung zeigt, wie eng Supportteam, Entwickler und Nutzer zusammen arbeiten müssen. Aus der Fallstudie werden Implikationen für die Praxis abgeleitet (z.B. dass Schnelligkeit bei Änderungen wichtiger ist als Fehlerfreiheit) und in das ALM-Modell eingearbeitet.
WiSo-Import:2015-03-26:546
Keywords: Innovation; Application Lifecycle Management; Anwendungsentwicklung; Akzeptanzkritische Anwendungen; Akzeptanz; Agiles Vorgehensmodell

At the Edge and Innovative – The Role of Boundary Innovators in Demographic Change - Danzinger, Frank; Dumbach, Martin; Möslein, Kathrin (European Academy of Management (EURAM) Conference, 2012)
WiSo-Import:2015-04-17:4251

Auf der Suche nach dem Service-Innovator - Möslein, Kathrin; Danzinger, Frank (2012)
WiSo-Import:2015-03-26:4305

BALANCE Konferenzband: Flexibel, stabil und innovativ: Arbeit im 21. Jahrhundert - Möslein, Kathrin; Trinczek, Rainer; Bullinger-Hoffmann, Angelika; Danzinger, Frank; Lücking, Stefan (Kathrin M. Möslein, Rainer Trinczek, Angelika C. Bullinger, Frank Danzinger , Stefan Lücking, 2012)
Der Konferenzband „Flexibel, stabil und innovativ – Arbeit im 21. Jahrhundert“ fasst die Beiträge zur 1. Jahreskonferenz des BMBF-Förderschwerpunkts „Balance von Flexibilität und Stabilität in einer sich wandelnden Arbeitswelt“ zusammen. Die 41 bundesweiten Projekte des Förderschwerpunkts untersuchen zwischen 2009 und 2013, wie sich die Chancen und Risiken, die beim Ausbalancieren von Stabilität und Flexibilität zur Förderung von Innovationsfähigkeit entstehen, nutzen und bewältigen lassen. Acht thematisch zusammengestellte Fokusgruppen, die durch das Metaprojekt „BALANCE - Flexibilität und Stabilität in der Forschungswelt“ begleitet werden, erarbeiten Ideen für Politik, Wirtschaft und Gesellschaft, die eine Entwicklung zukunftstauglicher Lösungen und Ansätze vorantreiben sollen. Das Buch wendet sich an Interessierte aus Forschung und Praxis der modernen Arbeitsgestaltung.
WiSo-Import:2015-09-23:4231

BALANCE Konferenzband: flexibel, stabil und innovativ - Möslein, Kathrin; Trinczek, Rainer; Bullinger, Angelika Cosima; Danzinger, Frank; Lücking, Stefan (Cuvillier, 2010)

Grenzinnovator-Communities: Innovationstreiber im demografischen Wandel - Danzinger, Frank; Dumbach, Martin; Sandig, Christian; Schmitt, C (2012)
WiSo-Import:2015-03-26:4281

Grenzinnovator-Communities: Innovationstreiber im demografischen Wandel - Staples, Ronald; Sandig, Christian; Danzinger, Frank; Dumbach, Martin; Wendelken, Anke; Schmitt, Claudia; Wabro, Sabine (2012)

Innovation Without Me: Why Employees Do (Not) Participate in Organizational Innovation Communities - Wendelken, Anke; Danzinger, Frank; Rau, Christiane; Möslein, Kathrin (RD Management Conference 2012, 2012)
WiSo-Import:2015-04-17:4260

Innovation without me: Why employees do (not) participate in organizational innovation communities - Wendelken, Anke; Rau, Christiane; Danzinger, Frank; Möslein, Kathrin (R & D Management, 2014)
A key issue in community research is the set of motivations stimulating individuals to participate and contribute voluntarily to communities. This article examines the motivations of employees, who are traditionally not involved in the innovation process, to (not) participate in organizational innovation communities. Building on an in-depth single case study, we aim to answer the following research questions: (1) What motivates participants of organizational innovation communities to participate? and (2) What motivates nonparticipants of organizational innovation communities to not participate? We find and categorize multiple factors that motivate non-research and development employees to participate and to not participate. Moreover, we find an overlap as well as differences in the set of motivations of participants and nonparticipants. With nonparticipants normally being a large but barely explicitly recognized group, we argue that the found deviations contribute to the understanding of motivations in the context of organizational innovation communities and allow for direct design implications for innovation managers. © 2014 RADMA and John Wiley & Sons Lt
WiSo-Import:2015-03-26:5298

Interaktive Kunden als Herausforderung: Die Fallstudie „JOSEPHS® – Die Service-Manufaktur“ - Roth, Angela; Fritzsche, Albrecht; Jonas, Julia; Danzinger, Frank; Möslein, Kathrin (HMD : Praxis der Wirtschaftsinformatik, 2014)
WiSo-Import:2015-03-26:5299

Kundeninteraktion in der frühen Phase des Innovationsprozesses durch virtuelle Interaktionsplattformen - Ihlenburg, Ditmar; Danzinger, Frank (HMD : Praxis der Wirtschaftsinformatik, 2010)
WiSo-Import:2015-03-26:514
Keywords: Innovation

Kundeninteraktionskompetenz in Industriegütermärkten - Danzinger, Frank (Gabler, 2010)
WiSo-Import:2015-04-13:2147
Keywords: organizational interaction; organizational learning; strategic orientation; customer interaction cometence; customer interaction cometence; organizational interaction; organizational learning; strategic orientation; customer interaction cometence; organizational interaction; organizational learning; strategic orientation

Kundeninteraktionskompetenz in Industriegütermärkten: Eine empirische Studie zur Interaktions- und Lernorientierung - Danzinger, Frank (Markt- und Unternehmensentwicklung, 2010)
WiSo-Import:2015-03-26:1814
Keywords: editedbooks

Mehr als nur Innovation - Effekte von Innovation Communities auf Wissensmanagement und intergenerationale Lernprozesse - Langer, M.; Danzinger, Frank; Möslein, Kathrin (2012)
WiSo-Import:2015-03-26:4282

Offen, innovativ & wertschätzend im demo-grafischen Wandel - Danzinger, Frank; Dumbach, Martin; Sandig, Christian; Schmitt, Claudia; Staples, Ronald; Wabro, Sabine; Wendelken, Anke (2012)

Open Innovation and Firm Performance: Investigating the Mediating Role of Social Capital - Raß, Matthias; Dumbach, Martin; Danzinger, Frank; Bullinger-Hoffmann, Angelika; Möslein, Kathrin (R&D Management Conference 2011, 2011)
WiSo-Import:2015-04-17:554
Keywords: social capital; Open innovation; Innovation; firm performance

Open Innovation and Firm Performance: The Mediating Role of Social Capital - Raß, Matthias; Dumbach, Martin; Bullinger, Angelika Cosima; Möslein, Kathrin; Danzinger, Frank (Creativity and Innovation Management, 2013)
This article examines the role of social relations and networks in open innovation settings. Building on extant open innovation literature as well as on social capital theory, we develop a model that conceptualizes social capital as a mediator between the implementation of open innovation instruments and firm performance. In doing so, this paper adds to the understanding of the role of structure and content of social relations in open innovation contexts as well as of sustainable side-effects of open innovation. In particular, we argue that apart from a direct effect of open innovation instruments on firm performance, there is also a mediated relationship between these variables. More precisely, we propose that the implementation of open innovation instruments strengthens an organization's social capital, which is, in turn, positively related to firm performance. s© 2013 John Wiley & Sons Lt
WiSo-Import:2015-03-26:4935
Keywords: Open innovation; performance; social capital

Open Innovation by opening embedded systems - Söldner, Constantin; Danzinger, Frank; Roth, Angela; Möslein, Kathrin (GeNeMe 2012, 2012)
WiSo-Import:2015-04-17:4265

Open Innovation – Communities zur Dienstleistungsentwicklung für Kunden und Mitarbeiter - Möslein, Kathrin; Danzinger, Frank (Dienstleistungsinnovationen offen sozial nachhaltig, 2013)
WiSo-Import:2015-04-20:4951

Rewiring Employees Through Innovation Communities – Investigating the Antecedents of Social Capital - Dumbach, Martin; Danzinger, Frank; Möslein, Kathrin (IPDMC, 2012)
WiSo-Import:2015-04-17:4268

Tools for collaborating and interacting in Living Labs - Perez Mengual, Maximilian; Jonas, Julia; Schmitt-Rüth, Stephanie; Danzinger, Frank (ServDes, 2018)
Living Labs serve as a novel form of collaborating and developing innovation. As interactive, physical settings, they hold several possibilities of facilitating co-creation with diverse stakeholders. Research on tools and methods used in Living Labs is still under development. To contribute to this research, this paper investigates the use of tools for interaction in a Living Lab. A longitudinal exploratory case study on the JOSEPHS® in Nuremberg was applied. This study finds that (1) there are three categories of tools used for integrating visitors, (2) interaction with visitors in a Living Lab depends on the factors time and commitment and (3) tools for different integration types need to be matched to the determinants of interaction. The study contributes to literature on co-creation and interaction in Living Labs by highlighting that visitor roles should not be perceived as fixed user categories, but as the variable result of interaction with applied tools.<br
Keywords: co-creation; living labs; tools; interaction

Towards Open Innovation in Embedded Systems - Söldner, Constantin; Roth, Angela; Danzinger, Frank; Möslein, Kathrin (AMCIS 2013, 2013)
By opening up a technology, firms can incorporate external actors to improve their products or to develop new applications on top of it. This phenomenon is discussed in the literature as open innovation (Chesbrough, 2003). An embedded system is an example of a modular and traditionally closed technology where parts of the system can be opened in order to stimulate innovation. In this paper, we want to explore how firms can pursue the opening of their embedded systems and their organization in order to unleash the potential of open innovation. By conducting twelve explorative interviews with experts in the field of embedded systems, we discovered three different forms of embedded systems openness and explored technical, internal and external organizational challenges associated with these three forms of openness. © (2013) by the AIS/ICIS Administrative Office All rights reserved.
WiSo-Import:2015-04-17:4949
Keywords: Embedded systems; Open innovation; Open technologies

Virtuelle Verkehrszeichen - Vom Trend zur Umsetzung nutzungsgerechter Verkehrsinformationssysteme - Nepper, Patrick; Danzinger, Frank (Humane Nutzung der Informationstechnologie, 2010)
WiSo-Import:2015-04-20:542
Keywords: virtual traffic signs; trend research; traffic management; Innovation